2021
DOI: 10.3389/fpsyg.2021.624254
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Breathing Techniques Into Psychotherapy to Improve HRV: Which Approach Is Best?

Abstract: IntroductionApproaches to improve heart rate variability and reduce stress such as breathing retraining are more frequently being integrated into psychotherapy but little research on their effectiveness has been done to date. Specifically, no studies to date have directly compared using a breathing pacer at 6 breaths per minute with compassion focused soothing rhythm breathing.Current StudyIn this randomized controlled experiment, 6 breaths per minute breathing using a pacer was compared with compassion focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…This breathing exercise is also known as six breaths per minute. Steffen et al confirmed that 5-5 breaths have a significant impact on increasing the work of the heart and reducing depression due to sudden panic attacks (Steffen et al, 2021). Heart rate has a close relationship with mood and mental disorders in individuals.…”
Section: Nada Android Application Developmentmentioning
confidence: 99%
“…This breathing exercise is also known as six breaths per minute. Steffen et al confirmed that 5-5 breaths have a significant impact on increasing the work of the heart and reducing depression due to sudden panic attacks (Steffen et al, 2021). Heart rate has a close relationship with mood and mental disorders in individuals.…”
Section: Nada Android Application Developmentmentioning
confidence: 99%
“…Co warte odnotowania, wydaje się, że leki psychiatryczne i psychoterapia, nawet jeśli skutecznie zmniejszają objawy w zaburzeniach afektywnych jedno-i dwubiegunowych, nie wpływają na poprawę w zakresie HRV. Wykazano jednak, że dodanie ćwiczeń oddechowych do psychoterapii prowadzi do takiej zmiany HRV [22].…”
Section: Dlaczego O Oddychaniu W Psychiatriiunclassified
“…Biofeedback helps increase awareness (Lehrer et al, 2007). People experiencing psychological stress also show increased physiological stress reactivity (Steffen, et al, 2014; Steffen et al, 2021). Through biofeedback, people become aware of muscle tension, respiration, heart rate, temperature, and skin conductance.…”
Section: Awareness and Resiliencementioning
confidence: 99%